Magnetic Micro/Nanorobots: A New Age in Biomedicines. (6th November 2022) - Liu, Dong; Guo, Ruirui; Wang, Bin; Hu, Jiawang; Lu, Yuan
Abstract : Micro‐/nanorobots have tremendous potential in biomedical applications, as they efficiently and accurately perform local diagnosis and targeted therapy. A magnetic field provides a wireless mean to drive and control micro/nanorobots. This method requires no fuel and is convenient for debugging, reconfiguration, and programmability; it is recyclable and allows nondestructive penetration of biological tissue. The successful integration of well‐designed robots, remote actuation systems, and imaging techniques has become a crucial step toward biomedical applications, particularly in vivo implementations. Herein, the fabrication methods of micro/nanorobots are examined, the driving mechanism of magnetic micro/nanorobots is explained, and the development of micro/nanorobots as transport tools to load and deliver drugs, biological reagents, and live cells is traced. Applications of these micro/nanorobots are expanding as surgical tools for sample collection, ophthalmic surgery, and biofilm degradation and as tools for in vivo and in vitro imaging relying on light, sound, and magnetism. Finally, the challenges faced by micro/nanorobots in in vivo applications and their future prospects are discussed. Abstract : Micro‐/nanorobots enter the body in a minimally invasive way to treat diseases, which provides a new idea for the development of modern biomedicine. Herein, the fabrication of micro/nanorobots, the motion mechanism driven by the magnetic field, and the latest progress in medical application are discussed. The future development and challenges of micro/nanorobots are further prospected.